The impact of the COVID-19 pandemic and policy support on productivity: A report of the ESCB Expert Group on productivity, innovation and technological change - Marianthi Anastasatu; Sofia Anyfantaki; Konstantins Benkovskis; Antonin Bergeaud; Maurice Bun; Simon Bunel; Andrea Colciago; Jan De Mulder; Davide Fantino; Beatriz González López-Valcárcel; Jiri Havel; Valerie Jarvis; et al. (European Central Bank (ECB), 2024)
This paper studies the short-term and long-term consequences of the COVID-19 pandemic for productivity in Europe. Aggregate and sectoral evidence is complemented by firm-level data-based findings obtained from a large microdistributed exercise. Productivity trends during the COVID-19 pandemic differed from past trends. Labour productivity per hour worked temporarily increased, while productivity per employee declined across sectors given the widespread use of job retention schemes. The extensive margin of productivity growth was muted to some degree by the policy support granted to firms. Firm entries declined while firm exits increased much less than during previous crises. The pandemic had a significant impact on the intensive margin of productivity growth and led to a temporary drop in within-firm productivity per employee and increased reallocation. Job reallocation was productivity-enhancing but subdued compared to the Great Recession. As confirmed by a granular data analysis of the distribution of employment subsidies and loan guarantees and moratoria, job reallocation and also debt distribution and "zombie firm" prevalence were not significantly affected by the COVID-19 policy support. The pandemic and related lockdowns accelerated changes in consumer preferences and working habits with potential long-term effects. Generous government support muted the surge in unemployment and reduced permanent scarring effects.
Keywords: D22; H25; J38; O47; 330; labour productivity; productivity-enhancing reallocation; COVID-19; adjustment of firms; government support; cross-country analysis; micro-distributedexercise; Europe